Balancing interests between freedom and censorship: Organizational strategies for quality assurance in science communication. (8th August 2022) - Fecher, Benedikt; Kuper, Freia; Fähnrich, Birte; Schmid-Petri, Hannah; Schildhauer, Thomas; Weingart, Peter; Wormer, Holger
Abstract: While science communication is increasingly being discussed as a third mission alongside research and teaching, there is little research on how universities and research organizations deal with issues regarding the quality of science communication. This article examines, from an organizational perspective, which new forms of quality assurance processes scientific organizations in Germany apply when addressing quality risks for science communication such as exaggeration in press releases or in the online communication of individual faculty members. Six focus group discussions were conducted with 22 participants (rectors or presidents of universities, heads of communication, ombudsmen, and high-impact researchers). Based on the results, proposals were developed to extend central as well as decentral organizational structures to assure good scientific communication practice. Their possible implementation was discussed in a workshop with representatives of all abovementioned groups. In conclusion, recommendations for future institutional policy are presented.